(untitled) (International Journal of Engineering and Computer Science, 2014)
In today’s world where the data and sensitive information is distributed over the networks, secure and strong cryptographic techniques should be employed to maintain integrity, authentication, and privacy of data. The aim of this paper is to propose a new design for a hybrid encryption algorithm by making use of both symmetric-key and asymmetric-key algorithms. We will use RSA, AES, and SHA-1 for this scheme.